Response of aquatic macroinvertebrate and aerial odonate assemblages to the removal of invasive alien trees in the Western Cape - Sharratt, Norma (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--University of Stellenbosch, 2005.